Spies : the epic intelligence war between East and West - Walton, Calder (abacus books, 2023)
"Spies is the history of the secret war that Russia and the West have been waging for a century. Espionage, sabotage, and subversion were the Kremlin's means to equalize the imbalance of resources between the East and West before, during, and after the Cold War. There was nothing "unprecedented" about Russian meddling in the 2016 US presidential election. It was simply business as usual, new means used for old ends. The Cold War started long before 1945. But the West fought back after World War II, mounting its own shadow war, using disinformation, vast intelligence networks, and new technologies against the Soviet Union. Spies is an inspiring, engrossing story of the best and worst of mankind: bravery and honor, treachery and betrayal. The narrative shifts across continents and decades, from the freezing streets of St. Petersburg in 1917 to the bloody beaches of Normandy; from coups in faraway lands to present-day Moscow where troll farms, synthetic bots, and weaponized cyber-attacks being launched on the woefully unprepared West. It is about the rise and fall of eastern superpowers: Russia's past and present and the global ascendance of China. Mining hitherto secret archives in multiple languages, Calder Walton shows that the Cold War started earlier than commonly assumed, that it continued even after the Soviet Union's collapse in 1991, and that Britain and America's clandestine struggle with the Soviet government provides key lessons for countering China today. This fresh reading of history, combined with practical takeaways for our current great power struggles, make Spies a unique and essential addition to the history of the Cold War and the unrolling conflict between the United States and China that will dominate the 21st century"--